Determinants of the Quality of Government Financial Reports (Study in Villages in North Belopa District) - Anugrah Sari, Rinda; Usman, Halim; Riyanti, Riyanti (JURNAL EKBIS, 2025)
This study analyzes the factors that influence the quality of village government financial reports in North Belopa District, focusing on HR competency and leadership style using a quantitative approach. Data were collected through questionnaires from 39 respondents who were fully selected, and analyzed with SPSS. The results show that the quality of financial reports is influenced by HR and effective leadership style to improve transparency and accountability of village financial reports.